Causality Analysis and Cointegration Between Mudharabah Financing and Return On Assets In Sharia Business Units Year 2016-2019 - Lubis, Delima Sari; Matondang, Zulaikha; Siregar, Hera Rusliani (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
In increasing profitability, Islamic banks can take advantage of productive assets in the form of financing. One of them is mudharabah financing, the higher the mudharabah financing , the higher the level of profitability of Islamic banks. However, based on data on mudharabah financing with return on assets obtained from the financial services authority, the amount of mudharabah financing always increases every year during the 2016-2019 period. Meanwhile, the percentage of return on assets decreased during that period. The purpose of this research is to find out whether the two variables influence each other or not . The research method is correlation analysis with data analysis techniques used, namely descriptive, normality test, stationary test, lag test, Granger causality test, cointegration test, vector autoregretion (VAR) model test, Impulse Response Function (IRF) test, and Variance Decomposition test. (VD) which is processed using Eviews 10. The results obtained from the causality test are that there is a one-way relationship between Mudharabah Financing and Return On Assets with a probability value of 0.0326 0.05 , but there is no causal relationship between Return On Assets and mudharabah financing.